Implementation of Clinical Supervision to Enhance Teacher Professionalism at Madrasah - Syahputra , Anggi; Sudadi; Mufaizin (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2024)
Clinical supervision serves as a powerful coaching method to enhance teacher professionalism by providing intensive guidance and direct, actionable feedback from supervisors. This study specifically examines the implementation of clinical supervision at Madrasah and assesses its influence on improving teachers’ professional competencies. Using a descriptive qualitative approach, data was gathered through structured observations and in-depth interviews with participating teachers and supervisors. Findings reveal that structured and consistent clinical supervision significantly bolsters teachers' understanding of effective teaching methods, enriches their instructional skills, and elevates overall classroom quality. Additionally, the direct interaction between supervisors and teachers allows for constructive feedback that is instrumental in helping teachers identify both their strengths and areas for development, fostering a reflective practice. Support from supervisors further motivates teachers to continually enhance their competencies in alignment with evolving educational demands. This study highlights that clinical supervision is not only an evaluation tool but also a developmental framework that positively impacts teacher professionalism at Madrasah Aliyah, aligning their practices with both academic and religious education standards.